Popular imagination and identity politics: reading the future in Star Trek: The Next Generation - Aoki, Eric, author; Ott, Brian L., author; Western States Communication Association, publisher (Colorado State University. Libraries, 2001)
Through an analysis of the popular syndicated television series Star Trek: The Next Generation, this essay begins to theorize the relationship between collective visions of the future and the identity politics of the present. Focusing on the tension between the show's utopian rhetoric of the future and its representational practices with regard to race, gender, and sexuality, it is argued that The Next Generation invites audiences to participate in a shared sense of the future that constrains human agency and (re)produces the current cultural hegemony with regard to identity politics. The closing section calls for critics to continue politicizing mediated images that appeal to popular imagination and to develop and implement a pedagogical practice of counter-imagination.
Brian Ott was a professor in the Department of Speech Communication at Colorado State University.
Keywords: identity politics; future; U.S. popular culture; imagination; utopian discourse